Implementation of the Reading-Reflection-Sharing Model in Developing Critical Literacy in Vocational High School Students - Qoyyimah, Dianatul; Husen, Mohammad; Susetya, Hemas Haryas Harja (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The lack of student literacy is a challenge for educators; therefore, the reading-reflection-sharing model exists to improve critical thinking skills. This study aims to describe the implementation, impact, and supporting and inhibiting factors of the Reading-Reflection-Sharing (RRS) model in improving critical literacy among vocational school students. This study employs a descriptive qualitative method that incorporates a case study design. Data collection uses observation, interview, and documentation techniques. The research subjects were grade X and grade XI vocational school SAQA students. Data analysis used data reduction, categorization, and presentation. The findings show that the RRS model not only improves academic understanding but also develops social skills, learning independence, and the delivery of ideas. This model has an impact on improving critical thinking skills, communication skills, and independent learning. Teachers, materials, and facilities support success, but time, low motivation, and undeveloped reflective habits hinder it. The reading-reflection-sharing model has been shown to develop students' critical literacy because it creates an interactive classroom environment, allows for sharing, and enables students to express their arguments more freely. This study utilizes the reading, reflection, and sharing models to enhance critical literacy studies. This study also offers alternative learning strategies that teachers can use to help improve students' critical thinking skills.